2005
DOI: 10.1097/01.inf.0000180574.18804.90
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Antiviral Response at 12 Months of Lopinavir/Ritonavir Therapy in Human Immunodeficiency Virus-1-Infected Children Experienced With Three Classes of Antiretrovirals

Abstract: Lopinavir/ritonavir when given as part of salvage regimen is well-tolerated, although switching to pills is frequently required. The regimen has a potent and durable antiretroviral activity in most heavily pretreated children, despite the presence of multiple mutations to all classes of oral antiretrovirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…We found that nearly half of them achieve virological response after rescue interventions. Our result are similar to other studies which also have been carried among children in real life situations [8,12]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that nearly half of them achieve virological response after rescue interventions. Our result are similar to other studies which also have been carried among children in real life situations [8,12]. …”
Section: Discussionsupporting
confidence: 93%
“…[7-9]. However, the extended use of PIs as salvage therapy for heavily pre-treated subjects has not fulfilled its expectations [10-12]. Moreover, there are few studies available concerning predictive factors of virological success when PIs/rit are used in a second or third-line of HAART in this special population [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…19 In another cohort of 45 PI-experienced children treated with LPV/r-based HAART, 42% had VL Ͻ400 copies/mL at 48 weeks. 20 The children in these previously mentioned studies were less sick than ours; fewer had AIDS and their median CD4% was much higher. In general, they were similar in age and baseline VL to our patients.…”
Section: Discussionmentioning
confidence: 81%
“…The recommended doses for children who weigh more than 15 kg are 10 mg/kg of body weight or 230 mg/m 2 (body surface area) twice daily, with a maximum of 400 mg per dose unless it is combined with drugs affecting cytochrome (CYP) P450 metabolism, which require LPV dose adjustment (4,28). Introduced as a salvage agent (22), LPV/RTV has become one of the preferred PI choices for first-line regimens in children Ͼ6 months of age in the countries with access to the drug.…”
mentioning
confidence: 99%